PENGARUH PENGGUNAAN LEMBAR KERJA SISWA (LKS) SEBAGAI MEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA PADA MATERI SISTEM PEREDARAN DARAH MANUSIA DI KELAS XI MIA SMA NEGERI 1 BANDAR PULAU TAHUN AJARAN 2021/2022 - Melinda Sari Sidauruk, Ade; Dianti Siboro, Thiur (Jurnal Metabio, 2022)
This study was conducted with the aim of determining the Effect of Using Student Worksheets (LKS) as a Learning Medium on Student Learning Outcomes in the Human Circulatory System Material in Class XI MIA of SMA Negeri 1 Bandar Pulau in the 2021/2022 Academic Year. The total population of class XI students was 113 students consisting of four classes and a sample of 50 students (2 classes) was taken randomly with purposive sampling. The research instrument used in data collection was a pre-test and post-test to determine the biology learning outcomes of class XI students of SMA Negeri 1 Bandar Pulau. From the results of hypothesis testing with the t-test, it was obtained |thitung| = 11.163. While ttable for df = 24, with a significance level of α = 0.05 is 2.064. So it can be concluded that |thitung| > ttable, namely 11.163 > 2.064, it can be concluded that Ha is accepted, H0 is rejected. This indicates a significant effect of the use of Student Worksheets on student biology learning outcomes. Based on the results of the Independent Sample Test, comparing the post-test scores of both classes, the significance value was 0.000 < 0.05. This concludes that there is a difference in the learning outcomes of students taught using Student Worksheets as a learning medium compared to those taught without them. The significant difference between the two scores can be seen from the average post-test scores. The test results showed that the average post-test score for the experimental class was 79.00, while the average post-test score for the control class was 61.60. The significant difference in the average scores between the experimental and control classes was 17.40.